Enhancing nursing students’ speaking confidence through role-play in English for healthcare communication - Burhan, Kristian; Astuti, Indri; Franchisca, Sherly; Amsa, Helfany (Universitas Islam Malang, 2026)
English communication has become an essential competence for nursing professionals in globalized healthcare systems. However, Indonesian nursing students often receive limited opportunities to practice authentic and confidence-building English speaking in medically contextualized situations. This research investigates the use of role-play in the English for specific purposes (ESP), English for Healthcare Communication course, responding to the limited opportunities for authentic and confidence-building speaking practice faced by Indonesian nursing students. The study sample of 44 students enrolled in a Diploma III Nursing Program at Akademi Keperawatan YPTK Solok employed a mixed-methods design with an explanatory sequential approach, emphasizing medically contextualized role-play activities. Quantitative data were pre- and post-intervention speaking tests, while qualitative information was obtained from questionnaires and interviews. Results indicated significant improvement in students' speaking performance, particularly in fluency, grammar, pronunciation, vocabulary, and comprehension. In addition, students reported higher confidence during medical communication performance. Interview data indicated that role-play enhanced students’ comfort with spontaneous English in nursing simulations, although the challenges of limited medical vocabulary and performance anxiety remained evident. The study found that role-play is an effective pedagogical approach in ESP contexts within an English for Nursing Program. In practice, role-play may be more effective when enhanced by digital simulations, increased scenario complexity, and reflective evaluation, whereas pre-designed role-play incorporating focused language instruction may further strengthen healthcare communication training.